2018
DOI: 10.1021/acsnano.7b07797
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Phagocytic Cell Sequestration by Tailoring Nanoconstruct Softness

Abstract: The effect of nanoparticle size, shape, and surface properties on cellular uptake has been extensively investigated for its basic science and translational implications. Recently, softness is emerging as a design parameter for modulating the interaction of nanoparticles with cells and the biological microenvironment. Here, circular, quadrangular, and elliptical polymeric nanoconstructs of different sizes are realized with a Young's modulus ranging from ∼100 kPa (soft) to 10 MPa (rigid). The interaction of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
103
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 39 publications
0
103
0
2
Order By: Relevance
“…A versatile fabrication strategy was used to realize polymeric nanoconstructs with controlled geometrical and mechanical features, including the size, shape, surface properties, and mechanical stiffness-the 4S parameters. These features can be independently tuned in the fabrication process to affect the therapeutic and imaging performances, as shown by the authors and other investigators (Key et al, 2013;Palomba et al, 2018). The first step in DPNs fabrication is the realization of a master silicon template through a Direct Laser Writer lithographic process.…”
Section: Fabrication and Physico-chemical Characterization Of The Dismentioning
confidence: 98%
See 2 more Smart Citations
“…A versatile fabrication strategy was used to realize polymeric nanoconstructs with controlled geometrical and mechanical features, including the size, shape, surface properties, and mechanical stiffness-the 4S parameters. These features can be independently tuned in the fabrication process to affect the therapeutic and imaging performances, as shown by the authors and other investigators (Key et al, 2013;Palomba et al, 2018). The first step in DPNs fabrication is the realization of a master silicon template through a Direct Laser Writer lithographic process.…”
Section: Fabrication and Physico-chemical Characterization Of The Dismentioning
confidence: 98%
“…Within this scenario, the authors have previously demonstrated a new nanotechnological platform-the Discoidal Polymeric Nanoconstructs (DPNs). Similarly to red blood cells, DPNs tend to resist sequestration by professional phagocytic cells, such us hepatic Kupffer cells and splenic macrophages (Palomba et al, 2018). This DPN feature results in longer circulation times and increased probability to lodge within the tortuous and low perfused tumor microvasculature (Key et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[381] Afterward, work by Decuzzi and coworkers revealed that the softness of backpacks also plays a role in suppressing their phagocytosis. [382] Guan and co-workers leveraged these concepts to fabricate different types of backpacks with various payloads using microcontact printing. [383] In 2015, Mitragotri and co-workers advanced their earlier work by showing that monocytes can deliver backpacks to inflamed areas in the body as a step toward immunotherapeutic applications (see Figure 14f for more recent iterations of backpacks made from PLGA).…”
Section: Leukocytesmentioning
confidence: 99%
“…[14][15][16] Materials chemists can elegantly engineer materials of various sizes, shapes, compositions and physicochemical properties. [17][18][19][20] Inorganic materials such as iron oxide nanoparticles, carbon nanotubes, metal organic frameworks, and mesoporous silica constructs, have been applied with good effect. 21 Biological materials are also being investigated including viral vectors for the delivery of gene-based therapeutics, and more recently extracellular vesicles have been receiving interest for drug delivery.…”
Section: Introductionmentioning
confidence: 99%